β2-Adrenergic Receptor Agonists in Diabetic Kidney Disease: Exploring a New Frontier - Shreya Hegde; Bharti Chogtu; Rahul Magazine; Ravindra Prabhu (Biochemistry Research International)
Diabetic kidney disease is a major cause of end-stage kidney disease. Various metabolic, hemodynamic, inflammatory, and profibrotic factors secondary to diabetes mellitus result in complex intracellular signaling, which in turn is responsible for the functional and structural changes associated with diabetic kidney disease. The beneficial effects of β2-adrenergic agonists on renal cells bearing β2-adrenergic receptors in diabetic kidney disease models have been reported. This narrative review explains the various mechanisms by which β2-adrenergic agonists can have potential beneficial effects on diabetic kidney disease and highlights various in vitro, animal and human studies which lend credence to this hypothesis. It also touches upon the challenges and future concerns regarding their use in patients with this condition.